Foraminíferos Bentônicos do Estuário de Cacha-Prego Ilha de Itaparica, Bahia, Brasil - ZERFASS, GEISE DE SANTANA DOS ANJOS; ANDRADE, EDILMA DE JESUS; LESSA, GUILHERME CAMARGO; MACHADO, ALTAIR DE JESUS (Pesquisas em Geociências, 2006)
The Cacha-Prego estuary is a spit built coastal feature of Holocene age located in the Itaparica Channel (Todos os Santos Bay, Bahia State) and does not present any river input, hence, any fresh water that flow into the estuary is associated with the seeping water table. The thalweg is under wide variations in salinity, characteristic of a mixohaline-euhaline environment. On the other hand, the upper intertidal areas showed salinity levels typical of euhaline environment. The benthic foraminifera assemblage is represented by 71 species, while the living microfauna is composed of 19 species. Most of the living species were found within mangrove swamps, at the upper intertidal level, which were not exposed to brackish low-tide flows. The foraminifera assemblage distribution in the Cacha-Prego estuary is heterogeneous and reflects different microhabitats. In spite of the importance of the allochthonous elements transported into the estuary by the prevailing flood tidal flows, the autochthonous elements, represented by common species typical of paralic environments, were dominant in the estuary.